Priority Strategy for Goat and Sheep Farming Development using IPA - Sulistya, Danang Wicaksana; Asnawi, Yudha Hermawan; Saptono, Imam Teguh (International Journal of Artificial Intelligence Research, 2025)
Designing a business model for sustainable goat and sheep  farming is one of the keys to increasing productivity and competitiveness of the livestock sector in Indonesia. This article examines the formulation of a business model based on upstream-downstream integration using the Importance Performance Analysis (IPA) tool to identify priorities that need more attention in the development of goat and sheep farming. The IPA matrix is used to evaluate important components based on the Grand Design for National Goat and Sheep Development 2045 and the Guidelines for the Implementation of the Goat and Sheep Corporation Development Program of the Directorate General of PKH, Ministry of Agriculture. The results of the analysis show that aspects of providing quality feed, strengthening cultivation management, and developing market communication and education are priority areas that need to be optimized. In addition, market demand analysis and logistics systems also need to be improved to support efficient and timely product distribution. Formulating a business model that integrates the entire agribusiness chain can increase efficiency, strengthen competitiveness, and support national food security.